Bouncy tiger: winnie the pooh first readers - Birkinshaw, Marie (Ladybird London, 1993)
"Bouncy Tiger" is a delightful children's story about a lively tiger who loves to jump and play. Full of energy, Bouncy Tiger explores the jungle, making friends with other animals along the way. Through his adventures, he learns about friendship, teamwork, and the joy of embracing his bouncy nature while also discovering the importance of taking turns and sharing fun with others.